Kajian Penerapan Prinsip-Prinsip Arsitektur Hijau Pada Bangunan Perkantoran (Studi Kasus Gedung Green Office Park 1, Bsd) - Haidar, Dziky; Syoufa, Ade (Jurusan Teknik Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 94118 e-mail :Jurusan Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 941, 2025)
The increase in the greenhouse effect is one of the most critical issues in the climate field, triggered by the construction of high-rise buildings and the widespread use of glass materials. The serious consequences of this phenomenon involve rising sea levels, melting polar ice caps, damage to ecosystems, and increased risk of infectious diseases. Therefore, research on the application of green architecture principles in offices is of great importance, especially through a case study on the Green Office Park 1 Building in BSD. The basis of this research involves understanding the adverse impacts of high-rise buildings and the use of glass materials on the environment and the greenhouse effect. The main objective of this research is to analyze how the Green Office Park 1 Building integrates the concept of green architecture, using a qualitative descriptive method. The results concluded that the building has not fully implemented the principles of green architecture, especially in paying attention to the condition of the building site.